Response of Three Legumes to Inorganic Fertilizer Application in Different Agro-Ecological Zones in Makueni County Kenya - Kerina , Arnold; Ngode , Lucas; Opile , Wilson; Mwamburi , Lizzy (African Journal of Education,Science and Technology (AJEST), 2017)
Legume productivity in Makueni County is low mainly due to declining soil fertility. Improving soil fertility through use of inorganic fertilizers can greatly increase grain legume productivity in the area. The objective of the study was to evaluate the effect of DAP fertilizer application on the productivity of three legume species in different agro-ecological zones in Makueni County. This study was conducted in Makueni County during the 2014 long rain season in three locations namely Machinery (IL6), Utafiti (LM5) and Mwanzo (LM4) with five farmers from each location. The three legume species were Beans (KAT/B-9), Cowpea (M66), Lablab (KAT/DL-1) and Lablab accession CP1 81364. The two DAP fertilizer treatments were 0 kg/ha (farmer practise) and 50 kg/ha (recommended practise). The experiment was laid out as a Randomised Complete Block Design (RCBD) with five replications. Data was collected on biomass yield at flowering and harvest and the grain yield. Data was subjected to ANOVA using SAS. Soil analysis results showed that the soils were deficient in nitrogen, phosphorous and organic carbon across the three sites. DAP fertilizer application significantly increased the biomass yield of KAT Bean-9. Harvest biomass yields increased by 49% and 100% in the three agroecological zones. Grain yield increased by 171 to 204% in the AEZs. DAP fertilizer application significantly increased cowpea M66 grain and biomass yields. Biomass yields increased between 63% and 96% in the three AEZs. Cowpea M66 grain yield increased by 60 to 127% in the three AEZs. DAP fertilizer application increased biomass accumulation of the two lablab varieties between 70% and 120%. Grain yields increased between 70% and 116%. The results from the study showed that farmers across three agro-ecological zones will greatly increase their legume yields if they adopted the use of inorganic fertilizer to improve soil fertility.